Pengaruh Employee Engagement terhadap Turnover Karyawan Gen Z Nolifa Collection Kota Solo - Anisa Fitri Ulhusna; Wahyu Utami (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
Establishing a company certainly has various twists and turns and challenges that cannot be avoided, for example, employee turnover which has been rampant for several decades.The number of samples consisted of 31 employees and was carried out at Nolifa Collection Solo City. The research instrument was the result of adopting the UWES and the turnover intention scale. The results of the study show (1) The level of employee engagement of Gen Z Nolifa Collection employees is mostly in the low category with a percentage of 35% and medium with a percentage of 55%. (2) The turnover rate of Gen Z Nolifa Collection employees is in the high category with a percentage of 74%. (3) this means that the lower the employee engagement, the higher the turnover and vice versa. The R-squared value is 0.363, indicating that employee engagement contributes 36.3% to turnover, with the remaining 63.7% influenced by other factors not examined.